Software Project Management (photo) - Hughes Bob (McGraw -Hill, 2006)
The risks of failure associated with development projects involving ICT( Information and Communication Technologies) are still of as much concern as they were ten years ago when thefirst edition of this book was pulished. The main concern of the book throughout its various editions has been to inculcate the fundamental practices of good project management needed by ICT practitioners as one of the foundations of their profectional education. While it is hoped that current practitioners will find much that will be heplful, the main target audiences for the book are computing and information systems on undergraduate and masters programmes.